A secure mechanism of group communication for pervasive grid. (24th September 2009) - Li, Yunfa; Jin, Hai; Han, Zongfen; Liu, Sanmin
Cooperative processing is a representative application in pervasive grid and group communication is the key technique in this application. It is a great challenge to ensure the security of group communication in pervasive grid. In this paper, we first describe the service infrastructure of middleware for pervasive grid. Then, we present a secure mechanism of group communication and analyse the correctness and the security of the mechanism. Finally, we verify the validity of this mechanism by experiments. Results show that our proposed mechanism is efficient to ensure the security of group communication in pervasive grid.